Glucocorticoid with or without additional immunosuppressant therapy for patients with lupus podocytopathy: a retrospective single-center study. (September 2015) - Hu, W X; Chen, Y H; Bao, H; Liu, Z Z; Wang, S F; Zhang, H T; Liu, Z H
Lupus podocytopathy is a newly recognized class of lupus nephritis characterized by extensive glomerular foot process effacement without capillary wall immune deposits. The treatment response and relapse of glucocorticoid with or without additional immunosuppressive agents has not been well investigated. In this study, 50 patients with lupus podocytopathy were included and received glucocorticoid alone (glucocorticoid monotherapy) or glucocorticoid plus additional immunosuppressive agents (combination therapy) for their induction or maintenance treatment regimens. The treatment response and relapse rate in the two groups were respectively analyzed. We found that the induction treatment with glucocorticoid monotherapy and combination therapy led to remission in 47 patients (94.0%) at 12 weeks treatment, with complete remission (CR) occurring in 38 patients (76.0%). The CR rate compared between glucocorticoid monotherapy and combination therapy showed no difference (76.7% vs 75.0%, p  = 0.9), the median time to CR was four weeks (range: 2.0–6.0 weeks) in glucocorticoid monotherapy and 8.0 weeks (range: 3.7–12.0 weeks) in combination therapy ( p  = 0.076). Twenty-seven of 47 patients (57.4%) relapsed during maintenance, the relapse rate was much higher in the glucocorticoid monotherapy group than in the combination therapy group (89.5% vs 35.7%, p  < 0.001), regardless of the induction regimens being glucocorticoid monotherapy or combination therapy. No patient developed end stage renal disease or died during follow-up for 6–125 months (median 62 months). In conclusion, the remission of lupus podocytopathy could be induced by glucocorticoid monotherapy or glucocorticoid plus other immunosuppressive agents, while the remission should be maintained by the combination regimen.